Role of Gender and Industry Experience in Construction Management Student Self-efficacy, Motivation, and Planned Behavior. Issue 1 (2nd January 2016) - Elliott, Jonathan W.; Thevenin, Melissa K.; Lopez del Puerto, Carla
ABSTRACT: The construction management (CM) profession is projected to grow over the next several years and a bachelor's degree coupled with industry experience produces the best CM employment prospects. Many CM undergraduate programs boast job placement rates of 90% to 100%, suggesting an unmet demand for graduates. Females are the largest untapped source of labor for the construction industry, yet are underrepresented at 6% to 10% of CM professionals and undergraduates. A young adult's decisions regarding career pathways and college attendance depend on several factors, including one's sense of self-worth. Self-efficacy and motivation are predictors of students' educational pursuits, persistence, and performance. This study investigated undergraduate CM students' (n = 587) construction education domain-level self-efficacy (CESE), motivation (CEM), and planned behavior (CEPB) by gender, as well as level of hands-on and management-based construction experience. Results of the t-test revealed the female CM students had higher CEM than their male counterparts (p = .025). ANOVA indicated student with hands-on and management-based construction experience reported higher level of CESE than those without experience (p = .002 and p = .027, respectively). ANOVA post-hoc analysis, study implication and limitations, as well as opportunities for further research are discussed.